Analisis Non Finansial Pendirian Bisnis Frozen Yoghurt di Cipta Rasa Farm Kabupaten Bogor, Provinsi Jawa Barat, Indonesia - Gandhi, Prima; Sani, Zahran Syauqi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Milk is an animal product produced by mammals.The world community, including Indonesia, needs the nutrients contained in milk. The milk commodity can be cultivated by the people of Indonesia. West Java Province is included among the three largest milk-producing provinces in Indonesia. One of the fresh milk producers in West Java Province is Cipta Rasa Farm (CRF). CRF was founded in 2001 in Karang Asem Barat, Citeureup District, Bogor Regency. CRF is capable of producing 100 liters of fresh milk. However, lately, CRF has left 20 liters of milk that are not sold out. In order to gain additional income, CRF plans to make frozen yogurt using leftover milk. This study aims to determine the non-financial feasibility analysis of establishing a frozen yogurt business unit on CRF in the form of a non-financial feasibility analysis consisting of analysis of product planning, marketing planning, production planning, organizational and management planning, and collaboration planning.The data used in this research are primary and secondary.This research's data analysis method is descriptive qualitative and quantitative. Based on the results of the non-financial analysis, it was concluded that the plan to establish a frozen yogurt business at Cipta Rasa Farm, Bogor Regency, was feasible.